Biodegradation of phenanthrene and pyrene using bacteria isolated from used vehicle lubricant-contaminated soil - Darma, Umar Zubairu (2017)
Petroleum industry contributes significantly towards global industrial civilization. Used vehicle lubricant oil being a petroleum product portrays dangerous impact on the environment as it generates hazardous polycyclic aromatic hydrocarbons (PAHs) through incomplete combustion. The rampant discharge of this oil in Malaysia causes serious environmental concern as PAHs are dangerous organic pollutants that cause mutation and cancer to living cells. The most commonly hazardous PAHs from used lubricating oil were phenanthrene and pyrene belonging to the low and high molecular weights PAHs. Biological removal of phenanthrene and pyrene provides an environmentally sound and state-of-the-art technique that employs natural biological processes for the complete elimination of such pollutants from the environment. However, slow degradation duration is a major PAHs biodegradation limitation. Therefore, the research objectives involved isolation of effective phenanthrene and pyrene degrading bacteria, optimizing the biodegradation conditions, analysing the biodegradation intermediates and evaluating the effects of heavy metals on the biodegradation effectiveness. Phenanthrene and pyrene degrading bacteria were initially isolated from used lubricating oil contaminated soil using enrichment and plating techniques where both PAHs served as the sole bacteria carbon and energy sources. The effective phenanthrene and pyrene degrading bacteria were screened based on spray plate technique and colorimetric assay followed by 16S rRNA gene identification using universal primers. The biodegradation conditions of such identified bacteria were then optimized using single factor optimization before subjected to response surface methodology based on full factorial central composite design (p ≤ 0.05). This was preceded with the analyses of phenanthrene and pyrene degrading metabolites using gas chromatography mass spectrophotometer (GC-MS). The identified bacteria were finally used for the formulation of bacteria consortium after the compatibility testing based on cross spread technique and permutation assessments through colorimetric assay. The consortium was then used to degrade 500 mg/L phenanthrene and 250 mg/L pyrene in a complex culture that contained varying concentrations (2 mg/L to 12 mg/L) of Nickel, Lead, Vanadium and Cadmium separately. Total of 93 different strains of bacteria were isolated from the enrichment technique. Among these bacteria, only 53 strains initiated the degradation of 5 g/L phenanthrene in 72 hours based on spray plate assessments (n = 3). Further screening by colorimetric assay indicated only two strains named MM045 and MM087 were able to degrade 75.2% and 80.2% of 500 mg/L phenanthrene in addition to 54.3% and 59.7% of 250 mg/L pyrene within 24 hours respectively (n = 3). These strains were then identified as Cronobacter sakazakii MM045 and Enterobacter sp. MM087 with accession numbers KT933253 and KT933254 respectively. The phenanthrene and pyrene degradation capabilities of C. sakazakii MM045 and Enterobacter sp. MM087 was statistically optimized through response surface methodology (p ≤ 0.05). This optimization showed the combined efforts of the independent variables from each of C. sakazakii MM045 and Enterobacter sp. MM087 culture resulted in 100% degradations of both phenanthrene (500 mg/L) and pyrene (250 mg/L) in 24 hours. These were validated experimentally using the numerical optimization analyses (n = 3). The phenanthrene and pyrene biodegradation intermediates were then identified using the GC-MS analyses (n = 3). The pyrene identified metabolites from the C. sakazakii MM045 and Enterobacter sp. MM087 degradation cultures include pyrene cis-4,5-dihydrodiol, 3,4-dihydroxyphenanthrene, phthalic acid, pyruvic acid, acetic acid, lactic acid and formic acid. Additionally, phenanthrene identified metabolites from both cultures were 3,4-dihydroxyphenathrene, phthalic acid, pyruvic acid, acetic acid and oxalic acid. These metabolites established the degradation pathways undergone by both bacteria. The bacteria were also found to tolerate more than 6 mg/L of Nickel, Cadmium, Lead and Vanadium which significantly exceeded the hazardous metals concentrations in the natural habitats were both bacteria survived prior to the isolation. Considering the effective phenanthrene and pyrene degradation responses of C. sakazakii MM045 and that of Enterobacter sp. MM087 in 24 hours, both isolates can be used for commercial applications of degrading PAHs from contaminated environments. This commercial application could be possible as all the optimized independent variables are achievable within natural environments such as soil and water bodies. Furthermore, environmental availability of the C. sakazakii and Enterobacter sp. portrays another desirable character that made their choice as the best degradation alternative. Additionally, both bacteria can maintain their degradation effectiveness even in a complex environment that contained concurrent contamination of PAHs and heavy metals. Therefore, C. sakazakii MM045 and Enterobacter sp. MM087 can effectively and rapidly degrade phenanthrene and pyrene from used vehicle lubricant contaminated environment.